Membentuk Karakter Pancasila di Era Generasi Z - Adelia Yusnita; Emilia Susanti; Salsabila Novita Sari; Putri Yulianisa; Tiara Anggraini; Sari Wahyuni Siregar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Indonesian state's ideology, known as pancasila, holds that the community must preserve moral principles. Pancasila serves as a manual for proper civic conduct. The purpose of this study is to ascertain how Generation Z, who have been impacted by globalization, use Pancasila values. A literature review is employed to carry out the strategy in this qualitative way of methodology. The focus of this essay is on the ways that Pancasila ideological values are vanishing in the lives of Generation Z, as well as the reasons for and effects of this phenomenon. This study aims to inform the public on the significance of living by Pancasila values, particularly in the light of the current globalization period.